2007
DOI: 10.2535/ofaj.84.83
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Study on the Tongue and Lingual Papillae of the adult Spotted Seal, Phoca largha

Abstract: Summary: We observed the external surface and connective tissue cores (CTCs) of the lingual papillae (filiform, fungiform and vallate papillae) of adult Spotted seals (Phoca largha) using SEM and light microscopy. The tongue was Vshaped and its apex was rather rounded. On the dorsal surface from apex to the one-third posterior of the tongue, the lingual mucosa was densely covered by filiform papillae, with a scatted distribution of dome-like fungiform papillae, which have orthokeratinized epithelium. At the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…On the other hand, Shimoda et al (1996), described the surface structure of the filiform papillae of the semi-aquatic Mustelid, Sea otter and noted that the surface structure of the filiform papillae of the Sea otter appeared to be conical shaped and lacked accessory protrusions. Smooth or lacking accessory protrusion on the filiform papillae has also been seen in the other aquatic Arctoidea, such as the California sea lion and Spotted seal (Yoshimura et al, 2002(Yoshimura et al, , 2007. These morphological differences may originate from not only their diets but also their living environment, i.e.…”
Section: Lingual Papillae and Their Connective Tissue Coresmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, Shimoda et al (1996), described the surface structure of the filiform papillae of the semi-aquatic Mustelid, Sea otter and noted that the surface structure of the filiform papillae of the Sea otter appeared to be conical shaped and lacked accessory protrusions. Smooth or lacking accessory protrusion on the filiform papillae has also been seen in the other aquatic Arctoidea, such as the California sea lion and Spotted seal (Yoshimura et al, 2002(Yoshimura et al, , 2007. These morphological differences may originate from not only their diets but also their living environment, i.e.…”
Section: Lingual Papillae and Their Connective Tissue Coresmentioning
confidence: 88%
“…The mixed dietary life is similar to some of other carnivore species such as raccoons and bears and morphological features especially the surface structure of filiform papillae may be representative of their masticatory method. Yoshimura et al (2002Yoshimura et al ( , 2007, observed the filiform CTCs of other aquatic Arctoidea, such as the Pinnipedia; California sea lion and Spotted seal. Filiform CTCs of the California sea lion appeared as thick conical shaped main processes, which were covered with numerous small rod-like secondary processes.…”
Section: Lingual Papillae and Their Connective Tissue Coresmentioning
confidence: 99%
“…CTC of filiform papillae in Pinnipeds seem to be varied compared with those in the terrestrial Arctoid; where CTCs of filiform papillae appear thick conical shaped with numerous small, studded projections but no concavities were found in front of the CTCs [California sea lion; Yoshimura et al, (2002)]. In contrast, filiform CTCs of the Spotted seal exhibit a primary core associated with approximately 5-15 accessory cores (Yoshimura et al, 2007) and are comparatively similar to terrestrial Arctoid species. Filiform CTC of Canidae, sister clade of Arctoidea, morphology also resembles that of the domestic dog with an oval concavity and a main protrusion situated on the posterior end of concavity (Kobayashi et al, 1992).…”
Section: Lingual Papillae and Their Connective Tissue Coresmentioning
confidence: 99%
“…Among other Arctoid species, the presence of fungiform CTC vary; fungiform CTCs of the Japanese black bear (Inatomi and Kobayashi, 1999) (Yoshimura et al, 2002) have a bulbous appearance with numerous small rod-like secondary cores being densely distributed on its surface. CTCs of fungiform papillae on the spotted seal's tongue (Yoshimura et al, 2007) appear as a cylindrical primary core with numerous rod-shaped accessory protrusions arranged on the lateral side of the cylindrical cores. Fungiform CTCs of the spotted seal had similarity with those in the Red panda and/or Japanese badger.…”
Section: Lingual Papillae and Their Connective Tissue Coresmentioning
confidence: 99%
See 1 more Smart Citation